Telling your story, together : musical collaboration as a resource for intellectually disabled persons who communicate without speech to express a self-determined narrative in music therapy - Lotter, Carol Barbara (University of Pretoria, 2024)
Mini-Dissertation (MMus (Music Therapy))--University of Pretoria, 2023.